2023
DOI: 10.3389/fenvs.2023.1105446
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ perception of the role of urban nature-based solutions and green infrastructures towards climate change in Italy

Abstract: Climate change in recent years is shaping society’s habits and life in large cities, then it will be necessary to plan and design nature-based urban solutions to meet different interests and needs. To enable this approach between cities, urban green spaces and climate change, sustainable and resilient urban growth models are needed, planned with the contribution of citizens as priority stakeholders. Citizens perceive and attribute value to Green Infrastructures (GIs), albeit in relation to different socio-econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…On the other hand, negative intercorrelations have been found between perceptions of climate change, awareness of climate change and NBS, perceptions of NBS, and willingness to engage. This finding is consistent with the study conducted by [42] in Italy, where they found that individuals who have a higher awareness of climate change are linked with greater positive perceptions towards NBS projects such as green infrastructure and willingness to contribute to its maintenance.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, negative intercorrelations have been found between perceptions of climate change, awareness of climate change and NBS, perceptions of NBS, and willingness to engage. This finding is consistent with the study conducted by [42] in Italy, where they found that individuals who have a higher awareness of climate change are linked with greater positive perceptions towards NBS projects such as green infrastructure and willingness to contribute to its maintenance.…”
Section: Discussionsupporting
confidence: 92%
“…This approach should involve not only landscape architects and urban planners but also social scientists, architects, arboriculturists, urban foresters, economists, meteorologists, and building engineers [61]. Lastly, our study lacks community involvement, which is essential for understanding the perceptions and preferences of NBS as perceived by the community, who will be the users of these regenerated spaces [17,62].…”
Section: Research Limitations and Strengthsmentioning
confidence: 99%
“…Questioning the preferred development model for European objectives and abandoning the narrative of the inevitable failure of the land of sprawl and extensive consumption [7][8][9] means understanding this dependency link and fostering a shift from a polyperiphery geography to a nonhierarchical, networked one [10]. The analysis outcomes can provide critical reflections on spatial and urban development perspectives at the European level, suggesting a change in mindset for all design and planning processes of the significant spatial transformations underway for climate change adaptation and mitigation [11,12]. To date, real estate and census values predominantly drive spatial developments, concentrating transformations towards the centres with the highest financial availability and the soils where the value is highest.…”
Section: Introductionmentioning
confidence: 99%